Erythrocyte complement receptor 1 (ECR1) and erythrocyte-bound C4d (EC4d) in the prediction of poor pregnancy outcomes in systemic lupus erythematosus (SLE). Issue 1 (5th September 2022) - Conklin, John; Golpanian, Michael; Engel, Alexis; Izmirly, Peter; Belmont, H Michael; Dervieux, Thierry; Buyon, Jill P; Alexander, Roberta Vezza
Abstract : Background: Complement activation has been associated with adverse pregnancy outcomes (APO) in SLE. Pregnant women with SLE were studied to evaluate whether complement dysregulation within the first two pregnancy trimesters predicts APO. Methods: Pregnant women fulfilled classification criteria for SLE. APO included neonatal death, preterm delivery before 36 weeks and small for gestational age newborn. Pre-eclampsia was also evaluated. Erythrocyte complement receptor 1 (ECR1) and erythrocyte-bound C4d (EC4d) were measured by flow cytometry. Complement proteins C3 and C4 were measured by immunoturbidimetry and anti-double-stranded DNA by ELISA in serum. Statistical analysis consisted of t-test, confusion matrix-derived diagnostic analysis, and multivariate logistic regression. Results: Fifty-one women had 57 pregnancies and 169 visits during the study. Baseline visits occurred mainly in the first (n=32) and second trimester (n=21). Fourteen (24.6%) pregnancies resulted in 21 APO with preterm delivery being the most common (n=10). ECR1 <5.5 net mean fluorescence intensity in the first trimester predicted APO with a diagnostic OR (DOR) of 18.33 (95% CI: 2.39 to 140.4; t-test p=0.04). Other individual biomarkers did not reach statistical significance. To estimate the likelihood of APO, we developed an algorithm that included the week of pregnancy, ECR1 and EC4d. From this algorithm, a Pregnancy Adversity Index (PAI) was calculated, and a PAI >0 indicated an elevated likelihood of pregnancy complications (DOR: 20.0 (95% CI: 3.64 to 109.97)). Conclusions: Low levels of ECR1 in early or mid-pregnancy are predictive of an APO. Incorporating the weeks of gestation and both ECR1 and EC4d generated a PAI, which further predicted serious pregnancy complications.